THE ARRIVAL OF THE STRANGE: MINING AND WATER CONFLICT IN RURAL COMUNITIES OF CAETITE AND-PINDAI-BAHIA, BRAZIL - Rodrigues, Fernanda Oliveira; Costa, Wesley Borges [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
This work aims analyze the water conflicts caused from the implantation of mining Project Iron Stone by the business Bahia Mining in the cities of authors that discuss the agrarian question in country, the territorial disputes and the water conflicts, as well as made use of field research composed for semi-structured interviews with peasants affected by such mining project. The text discusses the role of the state in economic territorial transformations in the backwoods productive of Bahia; the conflicts for water in rural comunities of Caetite and Pindai; and, finaly, present the data collected in the field whose speech of interviewees revels the actions in the process of disput for use and preservaction of water in rural comunities of Caetite and Pindai; and, finaly, present the data collected in the field whose speech of interviewees revels the actions in the process of disput for use and preservaction of water.
Keywords: Bahia; Productive backwoods; Territorial policies; Territorial Development